Computational Docking Analysis of Protein-Ligand Interactions in Diabetes-Related Complications: Targeting Molecular Pathways for Therapeutic Intervention (Journal of Advances and Scholarly Researches in Allied Education, 2024)
A key tenet of the scientific method is the integration of computational resources into the chemical and biological domains to facilitate the discovery and development of new pharmaceuticals. A major public health concern in India is diabetes. An immediate start is required to begin the research and development of a novel diabetic therapy. Type 2 diabetes remains incurable despite the availability of several therapies. Target identification, interactions between proteins and ligands, and residues in the active site form the basis of drug design. Our focus here is on five conserved and very active amino acid residues from five proteins with essential roles in diabetes. A variety of docking methods were used to investigate the binding mechanism and affinities of drug-like compounds, chalcones, some plant chemicals, and other potential anti-diabetic medications from the virtual screening database (ZINC) (free database). The protein data bank was searched for the three-dimensional structural coordinates of 1AH3 (Aldose Reductase) according to the results in literature and the Root Mean Square Deviation (RMSD).